2017
DOI: 10.1007/s00421-017-3751-5
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle and performance adaptations to high-intensity training in elite male soccer players: speed endurance runs versus small-sided game training

Abstract: PurposeTo examine the skeletal muscle and performance responses across two different exercise training modalities which are highly applied in soccer training.MethodsUsing an RCT design, 39 well-trained male soccer players were randomized into either a speed endurance training (SET; n = 21) or a small-sided game group (SSG; n = 18). Over 4 weeks, thrice weekly, SET performed 6–10 × 30-s all-out runs with 3-min recovery, while SSG completed 2 × 7–9-min small-sided games with 2-min recovery. Muscle biopsies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 61 publications
7
31
0
1
Order By: Relevance
“…The variability in load metrics across the microcycle has not been explored sufficiently within the literature, despite a plethora of studies quantifying competition variability (14,16). Changes in stimuli and load are important for training adaptations within the elite setting (24). Another area that has yet to be covered in detail is the contextualization of the microcycle, with most studies failing to provide any specific details of training sessions (e.g., the training session held the day before the match was referred to as match day [MD]-1 and included tactical preparation with set pieces).…”
Section: Introductionmentioning
confidence: 99%
“…The variability in load metrics across the microcycle has not been explored sufficiently within the literature, despite a plethora of studies quantifying competition variability (14,16). Changes in stimuli and load are important for training adaptations within the elite setting (24). Another area that has yet to be covered in detail is the contextualization of the microcycle, with most studies failing to provide any specific details of training sessions (e.g., the training session held the day before the match was referred to as match day [MD]-1 and included tactical preparation with set pieces).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the small to moderate within-group changes might be explained by muscular adaptation, including an increase in substrate (i.e. phosphocreatine), enzymatic activity 7,8 and alteration of contractile properties, 23 as well as potential neural adaptations (i.e. fibre recruitment, firing rate, motor unit synchronisation, recruitment of the gluteal muscle group).…”
Section: Discussionmentioning
confidence: 99%
“…Low-volume sprint interval training (SIT) might be appealing during the season where players can be exposed to maximalintensity activity through a reduced workload that also enables coaches to address technical and tactical aspects of the game. 6 It is well-documented that SIT (~20-30 s) offers an effective strategy for inducing rapid physiological remodelling 7,8 and increasing physical 'fitness' in athletic populations. 6,9 Moreover, improvements in intermittent-and endurance-based exercise performance have been observed after only two weeks of SIT, 6,10,11 and are attributed to morphological and metabolic adaptations within the skeletal muscle [10][11][12] and improved cardiorespiratory capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Fransson et al [26] showed remarkable changes in MCT-4 protein expression after 4 weeks of soccer specific training regimes like speed endurance (+30%) and small sided games (+61%) in well-trained soccer players. An increase in MCT-1 and MCT-4 density in skeletal muscle after 6 weeks of strength training was however merely reported by Juel et al [27].…”
Section: Introductionmentioning
confidence: 99%